International development assistance and the inclusivity paradox in fragile and conflictaffected states - Timothy Donais; Alistair D. Edgar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The principle of inclusive development lies at the heart of the Sustainable Development Goals (SDGs), and in particular Goal 16, with its focus on inclusive societies backed by inclusive institutions. Yet despite its ubiquity across the SDGs, inclusivity not only remains ill-defined, but is both controversial and deeply political across many UN member states. This is particularly so in fragile and conflict-affected states (FCAS), where the idea of sharing power more broadly (as one key element of what inclusivity implies) may be accepted in principle by elite-level actors but is rarely embraced in practice. In more extreme cases-South Sudan and Haiti among them- political power structures are dominated by elites determined to keep politics, through violence if necessary, as exclusive as possible. Within this wider context, in this paper we reflect on the challenges of operationalizing inclusivity and consider the strategies and policies through which development actors are navigating the dilemmas of operationalizing inclusivity in FCAS contexts. Drawing in part on evidence presented in draft chapters for a forthcoming volume on SDG 16 co-edited by the authors, we suggest that absent a consistent focus on inclusivity practices, the inclusivity principle risks becoming yet another underperforming buzzword in the development lexicon.
Keywords: 330; Sustainable Development Goals; inclusion; peacebuilding; fragile and conflictaffected states; practice turn